2013
DOI: 10.1515/jcim-2012-0011
|View full text |Cite
|
Sign up to set email alerts
|

The use of an anti-inflammatory supplement in patients with chronic kidney disease

Abstract: Chronic kidney disease (CKD) is characterized by a continuous reduction in kidney function, increased inflammation, and reduced antioxidant capacity. The objective of this study was to assess the effects of a herbal supplement on systemic inflammation and antioxidant status in non-dialysis CKD patients. Sixteen patients with CKD (56.0±16.0 yrs, 171.4±11.9 cm, 99.3±20.2 kg) were randomly chosen to receive a herbal supplement composed of Curcuma longa and Boswellia serrata, or placebo. Plasma levels of interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 61 publications
0
30
0
1
Order By: Relevance
“…Mohammadi, Kayedpoor, Karimzadeh‐Bardei, and Nabiuni () found out that anti‐inflammatory and antioxidative impacts of curcumin in patients with polycystic ovary syndrome is related to its function of inhibiting the gene expression of tumor necrosis factor‐α (TNF‐α), and reducing the circulating levels of CRP and interleukin‐6 (IL‐6). In addition, anti‐inflammatory effects of curcumin in patients diagnosed with metabolic syndrome have been demonstrated by others (Moreillon et al, ; Panahi et al, ). In a trial conducted on patients with tropical pancreatitis, curcumin ingestion at a dosage of 500 mg/day for 6 weeks significantly reduced malonyldialdehyde (MDA) concentrations and led to a significant increase in glutathione levels (Durgaprasad, Pai, Vasanthkumar, Alvres, & Namitha, ).…”
Section: Introductionmentioning
confidence: 77%
“…Mohammadi, Kayedpoor, Karimzadeh‐Bardei, and Nabiuni () found out that anti‐inflammatory and antioxidative impacts of curcumin in patients with polycystic ovary syndrome is related to its function of inhibiting the gene expression of tumor necrosis factor‐α (TNF‐α), and reducing the circulating levels of CRP and interleukin‐6 (IL‐6). In addition, anti‐inflammatory effects of curcumin in patients diagnosed with metabolic syndrome have been demonstrated by others (Moreillon et al, ; Panahi et al, ). In a trial conducted on patients with tropical pancreatitis, curcumin ingestion at a dosage of 500 mg/day for 6 weeks significantly reduced malonyldialdehyde (MDA) concentrations and led to a significant increase in glutathione levels (Durgaprasad, Pai, Vasanthkumar, Alvres, & Namitha, ).…”
Section: Introductionmentioning
confidence: 77%
“…Third, these natural antioxidants still have the problems related to nonspecificity, impurity, or potential side effect undetected yet. In fact, in a randomed clinical trial, a herbal supplement composed of Curcuma longa and Boswellia serrata was given to patients with chronic kidney disease, the data shown that the herb which helped to improve the levels of antioxidant activity is safe and tolerable for these patients (Moreillon et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The in vivo and in vitro results display significant levels of expression of various ECM components, such as PAI-1, α-SMA and Col I, all of which may be the downstream biological events of the TGF-β signaling pathway. Previous studies have indicated that curcumin influences cytokine secretion and inflammation in CKD patients (30,31); the current data indicated that curcumin exerts nephroprotective effects, at least partially, via anti-TGF-β signaling.…”
Section: Discussionmentioning
confidence: 60%